2000
DOI: 10.1105/tpc.12.7.1103
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Abscisic Acid and Ethylene Signaling Cascades

Abstract: We screened for mutations that either enhanced or suppressed the abscisic acid (ABA)-resistant seed germination phenotype of the Arabidopsis abi1-1 mutant. Alleles of the constitutive ethylene response mutant ctr1 and ethyleneinsensitive mutant ein2 were recovered as enhancer and suppressor mutations, respectively. Using these and other ethylene response mutants, we showed that the ethylene signaling cascade defined by the ETR1 , CTR1 , and EIN2 genes inhibits ABA signaling in seeds. Furthermore, epistasis ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
313
3
5

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 529 publications
(342 citation statements)
references
References 59 publications
21
313
3
5
Order By: Relevance
“…The ein2 and etr mutants are hypersensitive to ABA (Beaudoin et al, 2000;Ghassemian et al, 2000), which agrees with the observation that ein2 mutants were isolated as abi1-1 suppressors. The ctr1 mutant, which is characterised by a constitutive ethylene response, appeared among mutants selected as enhancers of the ABA insensitive mutant abi1-1 and ctr1 monogenic mutants are also slightly ABA resistant (Beaudoin et al, 2000). These observations, in combination with the non-dormant phenotype of the ein2 abi3-4 double mutant indicated that ethylene negatively regulates seed dormancy by inhibiting ABA action (Beaudoin et al, 2000).…”
Section: Genes and Factors Affected In Seed Dormancy/germinationsupporting
confidence: 90%
See 3 more Smart Citations
“…The ein2 and etr mutants are hypersensitive to ABA (Beaudoin et al, 2000;Ghassemian et al, 2000), which agrees with the observation that ein2 mutants were isolated as abi1-1 suppressors. The ctr1 mutant, which is characterised by a constitutive ethylene response, appeared among mutants selected as enhancers of the ABA insensitive mutant abi1-1 and ctr1 monogenic mutants are also slightly ABA resistant (Beaudoin et al, 2000). These observations, in combination with the non-dormant phenotype of the ein2 abi3-4 double mutant indicated that ethylene negatively regulates seed dormancy by inhibiting ABA action (Beaudoin et al, 2000).…”
Section: Genes and Factors Affected In Seed Dormancy/germinationsupporting
confidence: 90%
“…Often seeds that respond to ethylene are light sensitive for germination (Kepczynski and Kepczynska, 1997). Ethylene insensitive mutants such as etr and ein2 germinate less well or after a longer period of after-ripening than wild type (Bleecker et al, 1988;Beaudoin et al, 2000). The ein2 and etr mutants are hypersensitive to ABA (Beaudoin et al, 2000;Ghassemian et al, 2000), which agrees with the observation that ein2 mutants were isolated as abi1-1 suppressors.…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…In addition to the genetic interactions of ABA signaling with ethylene, gibberellins, and brassinosteroids signal transduction in embryonic and early postembryonic development (Beaudoin et al, 2000;Gazzarrini et al, 2004;Ghassemian et al, 2000;Zhang et al, 2009), novel roles of ABA signaling during pathogen infection and following defense responses against biotic stresses have been suggested (Asselbergh et al, 2008;Cao et al, 2011;Fujita et al, 2006;Ton et al, 2009). Jasmonic acid (JA) and salicylic acid (SA) are two major plant hormones regulating plant biotic stress signal transduction.…”
Section: Interaction Of Aba Signaling With Biotic Stress Response Patmentioning
confidence: 99%